Impact of Financial Inclusion on Economic Growth during the Period 2011–2021: A Cross-sectional Study of Lower-Middle- Income Countries - Alosheibat, Suleiman Daood; Banikhalid, Hmood H.; Alawneh, Ateyah (International Journal of Economics and Financial Issues, 2023)
This study explores the impact of financial inclusion in lower- and middle-income countries on the gross domestic product as a representative of economic growth for the period of 2011–2021 using the Autoregressive distributed lag (ARDL) method. The results indicate a negative effect between the percentage of adults (over 15 years old) who own a bank card, whether credit or debit cards (F2), and economic growth in the long run. The results also indicate a positive effect among the percentage of adults (over 15 years) who have deposit accounts in financial institutions (F1), the percentage of adults (over 15 years) who have obtained loans from financial institutions (F3), and economic growth in the long run. The coefficient of determination (R2) reached 74% and the corrected coefficient of determination reached 72%, indicating that the independent variables used in the model largely explain the economic growth in countries with below-average defects. In addition to a long-term equilibrium relationship between the study variables, the speed of adjustment in the short term to the long term takes place within 0.28877 per year.